KARMA POLICING: RE-IMAGINING WHAT WE CAN (AND CAN’T) POST ON THE INTERNET. - Burnam-Fink, Michael; Tiidenberg, Katrin; McKnight, John; Tekobbe, Cindy (AoIR Selected Papers of Internet Research, 2015)
Popular discourse and culture on the internet of 2014-2015 is well-removed from that envisioned by the pioneers, idealists, and many scholars of the medium in its formative years. Far from the “early days of a better nation,” a phrase of Alasdair Gray’s engraved upon the Scottish Parliament Building and often deployed in public discourse on social media during the 2014 campaign for Scottish independence, this past year has seen attention drawn to some of the worst of online behavior, from videos of beheadings, to rape and death threats, to the aggressive vitriol of what some regard as a backlash by young white men against the increased visibility of women, people of color, and those identifying with one or more non-hegemonic identities. Whatever today’s internet may be, it is not Barlow’s (1996) independent republic of cyberspace or Rheingold’s (1993) “virtual community” of the WELL, a homogeneous assemblage of white male late-Baby Boomer software engineers of libertarian bent. With global reach and diversity have come challenges to discourse traditions, cultures, and social identities engaging with each other over new platforms which enable and favor some discourses while challenging or suppressing others. Clashes are perhaps inevitable. However, the technologies and socio-technical practices which have given rise to conflict may also be used to address imbalances of power, to create if not the libertarian republics of 1990s imagining, then creative counterpublics of peer production in which official and dominant narratives are refuted, repurposed, or simply ignored. Presenter One describes GamerGate as a systemic problem enabled by the ubiquity of the internet in everyday life;; argues for a proactive counter-insurgency strategy rather than the passive ‘don’t feed the trolls’ conventional wisdom written into the terms of service (TOS) documents of many online platforms;; and suggests the implementation of a modified Bayesian filtering technique that has been successful in regard to reducing email spam to combat online harassment and trolling. Interrogating the February 2015 memes of “Left Shark,” “Llama Drama,” and “The Dress,” Presenter Two argues that collaborative meme-making can build solidarity and community, while countering anti- meme discourse and the “serious business” of the internet, by invoking collective whimsy and humor. Presenter Three takes on dominant ideologies around gender, embodiment, age, aesthetics, sexuality, body policing, and more by investigating the #over40 and #over50 women posting on Tumblr and Instagram arguing for a complicated notion of resistance through self image re/crafting of fitness, motherhood, and lifestyle among women over 25. Presenter four explores the rhetorical genre of the satirical review on Amazon.com as feminist resistance, and argues for the disruptive and counter-narrative affordances of social media comments contrasted with the conventional wisdom of the comments as a cesspool of abuse and trolling. Together, this panel presents a range of imagined alternatives to polarized and bitter online discourse, from perspectives of media and cultural studies, political philosophy, counterinsurgency theory, science and technology studies, and rhetorical genre theory. Problems of contemporary internet discourse - both textual and visual - and imagined alternatives are situated not only historically and theoretically but are also grounded in close analysis of technological affordances and constraints of media and platforms.